The Unnaturalistic Enthymeme: Figuration, Interpretation, and Critique after Digital Mediation. (1st March 2016) - Pfister, Damien Smith; Woods, Carly S.
Abstract : This essay theorizes the unnaturalistic enthymeme, an emergent argument formation surrounding analogico-digital photography. Instead of presuming the naturalism of images, we contend that contemporary audiences have a heightened awareness of the ways that digital photography is altered. Drawing on the quadripartita ratio, or four categories of change associated with rhetorical figuration, we explore a series of image controversies that denaturalize assumptions about photographic realism. We examine how contemporary protesters respond to this shift in interpretive conventions by making the unnaturalistic enthymeme visible through culture jamming commercial billboards. The unnaturalistic enthymeme does not supplant the naturalistic enthymeme, but instead enables a "hypersophistic" attitude in visual culture—one that decides the veridicality of photographs through argument instead of assumptions about technological objectivity.